If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 2 = 14x + -7 Reorder the terms: 2 + 11x = 14x + -7 Reorder the terms: 2 + 11x = -7 + 14x Solving 2 + 11x = -7 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 2 + 11x + -14x = -7 + 14x + -14x Combine like terms: 11x + -14x = -3x 2 + -3x = -7 + 14x + -14x Combine like terms: 14x + -14x = 0 2 + -3x = -7 + 0 2 + -3x = -7 Add '-2' to each side of the equation. 2 + -2 + -3x = -7 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = -7 + -2 -3x = -7 + -2 Combine like terms: -7 + -2 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| y=2x+1(X) | | 2(2x-4)=-20 | | 94.9536=20.3472+11.304h | | 15-(-42)= | | 880=2n^2-4n | | 1672.992=2*3.14*r^2+2*3.14*7.2*h | | 5(x+7)-6(x+6)=0 | | N^2=8n-16 | | t=2m(m) | | 3(5)+7(-6)= | | 1x-3=3x-13 | | y-6=2y-15 | | -5(-3p-4)=-70 | | 5-4(x-2)=12x-3 | | 24=2(v+2)+2v | | 2x+(-6)=3(2x-10) | | b^2+6b=-5 | | 8.1x-3.7=2.4x+2 | | 5x+16=5-5 | | 3(2-5m)=81 | | (-3+6i)(1+i)= | | P-19=34 | | -38=3(y-6)+2y | | 4x-7=4(x-3)+5 | | 8/n=12/15 | | 16x-7=13x+2 | | -38=8(y-6)+2y | | -4(6x+1)+6x=68 | | x=15-3x | | 2x^2+2y^2=10 | | -11=7w+8(w+8) | | 2v+11+2v+11+2v+11=76 |